2022
DOI: 10.1038/s41598-022-20322-4
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of how connectopic mapping reveals visual field maps in V1

Abstract: Functional gradients, in which response properties change gradually across the cortical surface, have been proposed as a key organising principle of the brain. However, the presence of these gradients remains undetermined in many brain regions. Resting-state neuroimaging studies have suggested these gradients can be reconstructed from patterns of functional connectivity. Here we investigate the accuracy of these reconstructions and establish whether it is connectivity or the functional properties within a regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 83 publications
(132 reference statements)
0
0
0
Order By: Relevance
“…For the primary visual network, both a principal connectopic gradient with an inferiorsuperior organisation and a secondary connectopic gradient with an anteriorposterior organisation were identified in the fetal cortex (Fig. 2A), consistent with connectopic mapping work in adults where two distinct gradients representing polar angle and eccentricity of vision are seen (Haak et al, 2018;Watson & Andrews, 2022). Assessing the global spatial similarity of each gradient across gestational age showed that the connectopic maps were remarkably replicable and symmetrical in topography, both across hemispheres and gestation, despite being derived independently (Fig.…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…For the primary visual network, both a principal connectopic gradient with an inferiorsuperior organisation and a secondary connectopic gradient with an anteriorposterior organisation were identified in the fetal cortex (Fig. 2A), consistent with connectopic mapping work in adults where two distinct gradients representing polar angle and eccentricity of vision are seen (Haak et al, 2018;Watson & Andrews, 2022). Assessing the global spatial similarity of each gradient across gestational age showed that the connectopic maps were remarkably replicable and symmetrical in topography, both across hemispheres and gestation, despite being derived independently (Fig.…”
Section: Resultssupporting
confidence: 83%
“…Globally, this organisation remains largely stable across the studied age range, suggesting that the organisation of these RSNs is shaped early in gestation and is intrinsically determined. This was most evident in the primary sensory and motor networks, which showed remarkably consistent connectopies across our study period of 25-37 GW that are already comparable to the canonical topographic organisation of functional connectivity in corresponding cortical regions in the mature adult brain (Haak et al, 2018;Ngo et al, 2021;Park et al, 2021;Watson & Andrews, 2022). Within this, we have identified local clusters of age-related differences in the gradient values, suggesting an on-going refinement of their connectivity structure.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…For instance, it has long been known that the brain has behaviourally relevant topographic organisations and regions may have multiple overlapping functional organisations (Kaas 1997; Jbabdi, Sotiropoulos, and Behrens 2013). Recently, various methods have been developed to investigate the ‘gradual’ organisation of the brain, see (Watson and Andrews 2022) for an overview and comparison of methods. These methods are termed ‘connectopic mapping’.…”
Section: Introductionmentioning
confidence: 99%